ANALISIS PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE KAHF DI KALANGAN MAHASISWA FEB UNIVERSITAS PANCASILA - Tyahya Whisnu Hendratni; Felix Sanggam Nainggolan (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2026)
This study aims to analyze the influence of price and product quality on the purchase decision of Kahf skincare products among students of the Faculty of Economics and Business, Pancasila University. The background of this research is based on the rapid growth of the skincare industry in Indonesia and the importance of understanding the factors that influence consumer purchasing decisions, particularly among students. This research uses a quantitative approach with a descriptive method. The research sample consists of 100 students from the Faculty of Economics and Business, Pancasila University, who have previously purchased Kahf skincare products. The data analysis technique employed is Structural Equation Modeling (SEM) with the assistance of SmartPLS software. The results indicate that price and product quality have a direct positive effect on purchase decisions. This research concludes that pricing strategies and product quality improvements need to be balanced to enhance consumer purchase decisions. The practical implications of these findings can be utilized by the Kahf brand management in designing more targeted marketing strategies.